2011
DOI: 10.1007/s10681-011-0562-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genotypic and yearly variations on fruit quality and functional traits for tetraploid table grape breeding

Abstract: We estimated genetic and environmental variance components for fruit quality traits (cluster weight, berry weight, soluble solids content, total sugar content, sugar composition, free acid content, total amino acid content, amino acid composition), and a functional trait (gamma-aminobutyric acid (GABA) content) of three commercial tetraploid table grape cultivars (Kyoho, Pione, Suiho) grown in Japan over three successive years. ANOVA showed that the effect of genotype was significant (P \ 0.05) for all traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…No significant increase in soluble solids and total sugar contents were observed in tetraploid grape berries (Shiraishi et al 2012), in contrast to the higher levels of soluble solids observed for tetraploid passion fruit (Rêgo et al 2011). In grapevine, these traits are highly influenced by the environment and exhibit low correlation to the genotype (Shiraishi et al 2012).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…No significant increase in soluble solids and total sugar contents were observed in tetraploid grape berries (Shiraishi et al 2012), in contrast to the higher levels of soluble solids observed for tetraploid passion fruit (Rêgo et al 2011). In grapevine, these traits are highly influenced by the environment and exhibit low correlation to the genotype (Shiraishi et al 2012).…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, shorter branches, larger stem diameters and smaller roots were described for autotetraploid plants from three Vitis rootstock cultivars, whereas, no morphological alteration was reported for allopolyploids (Motosugi et al 2002). Berry size and sensory and functional compound contents were also increased in tetraploid grape cultivars, in comparison to diploid ones (Shiraishi et al 2012(Shiraishi et al , 2010(Shiraishi et al , 2008. No significant increase in soluble solids and total sugar contents were observed in tetraploid grape berries (Shiraishi et al 2012), in contrast to the higher levels of soluble solids observed for tetraploid passion fruit (Rêgo et al 2011).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Polyploidization in grapevine could allow a greater fruit size and a loose berry cluster, characteristics that are very important for table grapes (Alleweldt and Possingham 1988). In fact, an increase in berry size and in the content of sensory and functional compounds in tetraploid table grape cultivars in comparison with their diploid counterparts has been reported (Shiraishi et al 2008(Shiraishi et al , 2010(Shiraishi et al , 2012, although without a significant variation in soluble solids and total sugar content (Shiraishi et al 2012). In addition, tolerance to environmental stress and the increased production of secondary metabolites could also be interesting in wine grapes.…”
Section: Introductionmentioning
confidence: 99%